Efficacy Perceived by Patients of Post-infarction Cardiovascular Rehabilitation Strategies - María Gabriela Balarezo García; Carlos Antonio Escobar Suárez; Becker Neto Mullo (Medisur)
Foundation: the assessment of the effectiveness of strategies for cardiac rehabilitation after a heart attack is of fundamental importance in the search for improvements in medical care and the health status of patients. Objective: to identify the effectiveness of three post-infarction cardiovascular rehabilitation strategies perceived by patients with a history of acute myocardial infarction. Method: a descriptive, cross-sectional and correlational study was carried out. The study population was made up of 90 patients who participated in post-infarction cardiac rehabilitation programs implemented in the medical facilities of the Ecuadorian Institute of Social Security in the Sierra region of Ecuador. The technique for data collection was the survey. Friedman and Wilcoxon statistical tests were used for correlation analysis. Data were presented in quantities and percentages. Results: patients perceived group cardiac rehabilitation and lifestyle education as the most effective (mean score: 9.56 and median: 10). The Friedman test showed statistically significant differences (p < 0.01) between the evaluations of each of the strategies. According to the Wilcoxon test, there were statistically significant differences between the evaluations of the three strategies (z ≠ 0; p < 0.000). Conclusions: there were differences in the perception that patients with a history of acute myocardial infarction had about post-infarction cardiovascular rehabilitation strategies. Group cardiac rehabilitation and lifestyle education were perceived as most effective.